Leonora Falbetti sulle scene di corte tra Firenze e Parigi (1654-1662) - Spinelli, Leonardo (Drammaturgia, 2020)
The archival documents of the Medici fund kept at the State Archive of Florence, allow us to reconstruct the biography and a large part of the career of the Florentine soprano Leonora Falbetti. Leonora belonged to a ‘family of art’ that between the 17th and 18th centuries worked within an international performance circuit that connected the Italian theatres with the French and Imperial ones: it also included her older sister Lisabetta and her son Francesco (born by her husband and semi-professional actor Carlo Ballerini). The essay proposed here, traces the professional steps that allowed Falbetti to earn the prestigious call to perform in Paris in the Ercole amante in 1662. This was the most important performance of the exceptionally long celebrations for the marriage between Louis XIV and the Infanta of Spain Maria Teresa of Habsburg.